RuvAB-directed branch migration of individual Holliday junctions is impeded by sequence heterology - Dennis, Cynthia (Nature Publishing Group, 2004)
The Holliday junction, the key intermediate of recombination, is generated by strand exchange resulting in a covalent connection between two recombining DNA molecules. Translocation of a Holliday junction along DNA, or branch migration, progressively exchanges one DNA strand for another and determines the amount of information that is transferred between two recombining partners. In Escherichia coli, the RuvAB protein complex promotes rapid and unidirectional branch migration of Holliday junctions. We have studied translocation of Holliday junctions using a quantitative biochemical system together with a ‘single-molecule' branch migration assay. We demonstrate that RuvAB translocates the junctions through identical DNA sequences in a processive manner with a broad distribution of individual branch migration rates. However, when the complex encounters short heterologous sequences, translocation of the Holliday junctions is impeded. We conclude that translocation of the junctions through a sequence heterology occurs with a probability of bypass being determined both by the length of the heterologous region and the lifetime of the stalled RuvAB complex.